A STUDY OF STUDENT PERSEPECTIVES ON ACHIEVEMENT MOVITATION IN LEARNING ENGLISH AT KWIK KIAN GIE SCHOOL OF BUSINESS IN NORTH JAKARTA - Yosef Dema; Elisabeth Vita Mutiarawati; Yohanes Langgar Billy (Jurnal Komunikasi dan Bisnis, 2022)
The most important aspect in achieving linguistic goals is motivation. The purpose of the research is to learn about the students' motivation for accomplishing their English class goals. Purposive sampling was used throughout the study, which lasted from 2019 to 2021. Thirty students were interviewed carefully and semi-structured for data. The following three questions were posed to all participants: “How confident are the students in achieving good learning outcomes?”, “What motivates them to achieve these outcomes?”, and “What tactics are used to achieve expected results?” The data was analyzed using the traditional content analysis method. Positive and negative attitudes, intrinsic and extrinsic impulses, and principled eclecticism tactics all lead to good or bad learning results, according to the study. Lecturers should foster students' positive attitudes toward learning, increase their integrative and instrumental drives, and encourage students to use a variety of learning methodologies in order to obtain great academic results.